Analisis Dampak PKH dalam Peningkatan Kualitas Hidup Masyarakat Kelurahan Tegal Sari Mandala Ii, Kecamatan Medan Denai - Boy Dippu Tua Simbolon; Kezia Thasa Emteta Karina Bangun; Stefy Margaretha; Zoan Gaharu Perangin-angin; Halking Halking (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study was conducted to analyze the impact of the Family Hope Program (PKH) on improving the quality of life of the community in Tegal Sari Mandala II Village, Medan Denai District. This program is expected to strengthen the welfare of poor families by improving access to health services and education, as well as the economic resilience of recipient households. The study used a descriptive method with a qualitative approach to in-depth describe the experiences and changes experienced by beneficiary families. Data were obtained through in-depth interviews and field observations. The findings indicate that PKH contributed to increased utilization of maternal and child health services, increased school participation of beneficiary children, and improved family economic capacity, although not yet optimal. The implications of this study emphasize the importance of strengthening mentoring, improving the quality of basic services, and optimizing the role of local governments so that PKH can have a more sustainable impact on community welfare.